Evolution of Aroma Profiles in Vitis vinifera L. Marselan and Merlot from Grapes to Wines and Difference between Varieties - Yi-Lin Ge; Nong-Yu Xia; Ya-Chen Wang; Hua-Lin Zhang; Wei-Ming Yang; Chang-Qing Duan; Qiu-Hong Pan (Molecules, 2024)
The fermentation process has a significant impact on the aromatic profile of wines, particularly in relation to the difference in fermentation matrix caused by grape varieties. This study investigates the leaching and evolution patterns of aroma compounds in Vitis vinifera L. Marselan and Merlot during an industrial-scale vinification process, including the stages of cold soak, alcohol fermentation, malolactic fermentation, and one-year bottle storage. The emphasis is on the differences between the two varieties. The results indicated that most alcohols were rapidly leached during the cold soak stage. Certain C6 alcohols, terpenes, and norisoprenoids showed faster leaching rates in ‘Marselan’, compared to ‘Merlot’. Some branched chain fatty-acid esters, such as ethyl 3-methylbutyrate, ethyl 2-methylbutyrate, and ethyl lactate, consistently increased during the fermentation and bottling stages, with faster accumulation observed in ‘Marselan’. The study combines the Orthogonal Partial Least Squares-Discriminant Analysis (OPLS-DA) model based on odor activity values to elucidate the accumulation of these ethyl esters during bottle storage, compensating for the reduction in fruity aroma resulting from decreased levels of (E)-β-damascenone. The ‘Marselan’ wine exhibited a more pronounced floral aroma due to its higher level of linalool, compared to the ‘Merlot’ wine. The study unveils the distinctive variation patterns of aroma compounds from grapes to wine across grape varieties. This provides a theoretical framework for the precise regulation of wine aroma and flavor, and holds significant production value.